2014
DOI: 10.1002/2013jb010609
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent modeling of slow slip events and associated seismicity and tremor at the Hikurangi subduction zone, New Zealand

Abstract: We present a time‐dependent slip model of 12 slow slip events (SSEs) occurring in the Hikurangi margin of New Zealand during 2010 and 2011. This model is obtained by inverting daily GPS solutions from GeoNet's continuous GPS network on the North Island and northern South Island. We compare the properties of these SSEs to observations in Japan, Cascadia, and Mexico and find that Hikurangi SSEs have comparatively large amounts of slip (up to 27 cm), high slip rates (up to 1.4 cm/d), and a large range of depths (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 73 publications
5
107
0
Order By: Relevance
“…An especially large tremor burst occurred from the end of 2010 to the beginning of 2011. An SSE occurred at the up-dip region of tremor activity in 2010, though there is a few months lag between the occurrence of SSE around tremor hypocenters and the activation of tectonic tremor (Bartlow et al 2014). …”
Section: Results Of Tectonic Tremor Detectionmentioning
confidence: 98%
“…An especially large tremor burst occurred from the end of 2010 to the beginning of 2011. An SSE occurred at the up-dip region of tremor activity in 2010, though there is a few months lag between the occurrence of SSE around tremor hypocenters and the activation of tectonic tremor (Bartlow et al 2014). …”
Section: Results Of Tectonic Tremor Detectionmentioning
confidence: 98%
“…In this study, we found that aftershocks occurred not only in regions partially overlapping the major afterslip but also among patches practically devoid of afterslip (Figure b). This is consistent with recent observations that both tremor and microseismicity are outside of the main slip regions during slow‐slip events along the Hikurangi subduction zone in New Zealand [ Bartlow et al ., ], due to static stress changes outside the slow‐slip region. However, alternative models, such as pore fluid diffusion, cannot be ruled out without further detailed analysis or modeling [ Bosl and Nur , ; Hainzl et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…The NIF has been employed to recover the spatiotemporal evolution of many SSEs (e.g., Bartlow et al, 2011Bartlow et al, , 2014Liu et al, 2010Liu et al, , 2015Miyazaki et al, 2006Miyazaki et al, , 2003Murray & Segall, 2005;Schmidt & Gao, 2010). However, previous studies have shown that the NIF often applies excessive smoothing to the accelerating or decelerating slip due to temporal smoothing of the slip (Fukuda et al, 2004(Fukuda et al, , 2008, thereby making it difficult to accurately retrieve the nucleation and subsequent evolution of the SSEs.…”
Section: Research Articlementioning
confidence: 99%